2021
DOI: 10.1177/1177180121995166
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability context and well-being factors of Indigenous community development: a study of Peninsular Malaysia

Abstract: The Indigenous people of Malaysia are a heterogeneous community scattered over more than 852 villages in Peninsular Malaysia. This community has been identified to be among the poorest and marginalized in Peninsular Malaysia. This study evaluates the well-being factors as well as problems that hinder the development of an Indigenous community in Peninsular Malaysia. This article adopted a quantitative approach based on data collected through survey and 2,136 respondents were interviewed. The study reveals that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
(52 reference statements)
1
15
0
Order By: Relevance
“…This study expands [26] notion of success for the Orang Asli. Figure 2 illustrates the amalgamation of two main facets of success in education for these Orang Asli.…”
Section: Success As a Concept For The Orang Asli In Educationsupporting
confidence: 64%
“…This study expands [26] notion of success for the Orang Asli. Figure 2 illustrates the amalgamation of two main facets of success in education for these Orang Asli.…”
Section: Success As a Concept For The Orang Asli In Educationsupporting
confidence: 64%
“…After World War II ended in 1945, Malaysia's concern was on alleviating poverty. After more than six decades of independence, Malaysia has managed to reduce her poverty level to 3.8% in 2009 (Hatta and Ali, 2013), however many indigenous communities are still living below National hardcore poverty line (Saifullah et al, 2021). These communities often face crop depredation and other types of conflict with wild elephants, although most are still influence by their ancestor's culture that imbued respect for the elephants (Lim, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The HEC faced by the oil palm plantations occurred since the nineteenth century when Malaysia introduced a rural settlement scheme to reduce poverty and to promote national economic growth (Ahmad Zafir and Magintan, 2016). Poverty rate has since reduced (Hatta and Ali, 2013) but is still prevalent among the Indigenous communities (Saifullah et al, 2021 We duly acknowledge that the intrinsic value of a wild elephant calculated here is purely an academic exercise and that the existence of any endangered species individuals is deemed priceless by the conservation communities (Soule, 1985) and any concerned citizen. However, in an effort to move the larger society toward supporting biodiversity conservation, increasingly the language of economics is used to justify the need for conservation despite challenges in capturing the complex relationship between nature and people via invisible and intrinsic values in addition to direct and indirect economic benefits (Kareiva and Marvier, 2012;Dasgupta, 2021).…”
Section: Povertymentioning
confidence: 94%
“…The increasingly high social pressure may pose threat to their source of livelihood. Several studies have concluded that indigenous people in Malaysia tend to remain poor due to insufficient access to basic education and the inability to work and receive housing and other infrastructure support (Saifullah et al, 2021). The socio-economic needs of the Orang Asli are not handled properly (Ismail et al, 2019).…”
Section: The Dynamics Of Charcoal Production Businessmentioning
confidence: 99%